Network model for the numerical solution of groundwater flow: Application to partially penetrating retaining structures in geotechnical engineering. Issue 4 (23rd May 2019) - Martínez‐Moreno, Encarnación; Alhama Manteca, Iván; García‐Ros, Gonzalo
Abstract : Based on the network simulation method, a precise numerical model is designed for the 2‐D groundwater flow in porous and isotropic aquifers. If a partially penetrating impervious barrier exists, groundwater will flow downstream circumventing the underground structure. The network model is solved numerically in a circuit simulation free code. Due to the powerful mathematical calculation algorithms implemented in is this type of codes, the provided solutions are quite precise for a relatively small grid size, with practically negligible computing times. The proposed model is applied to illustrative problems, providing hydraulic isopotential and stream lines, showing that as the dam penetration depth increases, the hydraulic gradient downstream decreases, thus reducing the risk of hydraulic failure.